Identifikasi Isolat Aspergillus sp. KRM 43 dari Madura dan Produksi Enzim Protease dengan Variasi pH dan Waktu Inkubasi - Nopvita Windi Astuti; MG. Isworo Rukmi; w wijanarka (Jurnal Akademika Biologi, 2015)
Proteases is an enzyme that has a high economic value, because they widely used for application in the field of industry.Protease can be generated from microorganisms, one of protease producer is derived from the genus Aspergillus. Aspergillus sp. KRM 43 that has isolated from alkaline soil can be predicted capable to produce alkaline protease. The purpose of this study was  to know the optimum of pH and incubation time for enzyme production from the mould. This research was conducted using a  factorial Randomized Complete Block Design with two factor i.e. a pH of 7, 8, 9 and incubation time of 5, 6, 7 days. Data collected were analyzed using Anova (α 0,05). The mould isolate were identified by observing its macroscopic and microscopic morphology. The result showed that Aspergillus sp. KRM 43 was identified as Aspergillus parasiticus. In this study showed pH treatment hadn't been  able to affect the production of protease. The highest proteases alkaline production of A. parasiticus KRM 43, found at 7 days incubation with proteases activity 2.24 U/mL and the specific activity 7.23 U/mg.Key words: Proteases, Aspergillus parasiticus, pH, incubation time